Bentuk Komunikasi Organisasi terhadapTingkat Okupansi Penumpang PT KAI Divisi Regional I Sumatera Utara - Mutiah; Fransisco Sidabalok, Jesaya (Paradigma, 2025)
The abundance of transportation in North Sumatra Province has caused public interest in using public transportation to be unstable, especially the use of trains. PT. KAI DIVRE I North Sumatra is one of the intercity transportation services operating trains, making it a business competitor for other companies in increasing passenger occupancy. This study aims to determine the integrated marketing communication strategy of PT. KAI DIVRE I North Sumatra in increasing passenger occupancy. The method used in this study is a case study with a qualitative approach using data collection techniques through in-depth interviews, observation, and documentation studies. This study uses the integrated marketing communication theory by Kotler and Keller (2016), which consists of advertising, sales promotion, events and experiences, public relations and publicity, online and social media marketing, personal selling, direct marketing, and mobile marketing. Based on the results of the research on the integrated marketing communication strategy of PT. KAI DIVRE I North Sumatra, it was found that in increasing passenger occupancy, the direct marketing dimension was quite influential because direct marketing is persuasive to potential buyers who are directly involved, even though it is integrated with the event dimension and other dimensions.